Arterial Events in Patients with Chronic Myeloid Leukemia Receiving Treatment with Second Generation Tyrosine Kinase Inhibitors - GA Gusarova; AG Turkina (Клиническая онкогематология)
Target therapy of chronic myeloid leukemia (CML) by tyrosine kinase inhibitors (TKI) allows to achieve high rates of the overall survival in CML. The choice of TKI treatment in every particular case should be based on individual CML patient’s characteristics, including comorbidities and the risk of adverse events (AE). Every TKI has a particular toxicity profile depending on off-target action spectrum. A probability of arterial AEs on TKI therapy is comparatively low but they may be life threatening. It is highly important to evaluate this kind of AEs during a long period of vascular TKI exposure. The age-specific increased incidence of cardiovascular and respiratory diseases is an additional factor in these patients with high overall survival on TKI therapy. The article is devoted to the analysis of frequency, mechanisms, particular features, methods of diagnostics and treatment of arterial AEs emerging on second generation TKI (nilotinib and dasatinib) therapy. The detailed characteristics of arterial occlusive events on nilotinib therapy and pulmonary arterial hypertension on dasatinib are presented. Special attention is paid to the analysis of risk factors of vascular AEs and the ways to correct modified risk factors. Timely assessment of clinical symptoms of cardiopulmonary, ischemic diseases/complications, and metabolic disorders helps to find specialized medical care (by a cardiologist, pulmonologist, endocrinologist), to prescribe an adequate therapy, provide prevention of complications and make decision about TKI dose adjustment/switching to alternative TKI being a true foundation of safe personalized treatment in CML patients.